FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN MASYARAKAT TERHADAP PROTOCOL KESEHATAN COVID-19 DI KELURAHAN PANGOLOMBIAN KECAMATAN TOMOHON SELATAN KOTA TOMOHON - Lumowa, Silvana Jinny Damaris; Bawiling, Nancy; Mamuaja, Prycilia P. (JURNAL ILMIAH KESEHATAN MANADO, 2024)
Background: The Covid-19 (Coronavirus Disease-2019) pandemic caused by the SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2) virus is an event that threatens public health in general and has attracted world attention. For data on positive Covid-19 sufferers in Pangolombian subdistrict, based on data from the Pangolombian subdistrict health center, there were 58 cases, 57 people recovered and 1 person died. Objective: To find out the factors that influence community compliance with the Covid-19 Health Protocol in Pangolombian Village, South Tomohon District, Tomohon City. Methodology: This research uses quantitative methods with an analytical survey design with a cross sectional study design which was conducted in February 2022. Sampling used Non Probability Sampling, namely "accidental", that is, sample selection was carried out by chance meeting. Data analysis was carried out univariate and bivariate (Chi-Square test). Results: Factors that have a significant influence on compliance with Covid-19 health protocols are knowledge (p-value=0.001<0.05 and OR=12.487), attitude (p-value=0.005<0.05 and OR=7.778 ), family support (p-value=0.000<0.05 and OR=20.156). Conclusion: From the conclusions that can be obtained, the factors that influence compliance with the Covid-19 health protocol in Pangolombian Village, South Tomohon District, Tomohon City are knowledge, attitudes and family support.